Density, Distribution and Population Structure of Apple Golden Snail (Pomacea canaliculata L.) in Organic and Conventional Paddy field Ecosystems - Vira Kusuma Dewi; Brinadia Solihati; Wawan kurniawan; Ceppy Nasahi; Nur Fitrianti (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2021)
Golden snail is one of the important pests that attack paddy crops. The structure of golden snail is divided into 3 based on the size of the shell diameter, namely juveniles (0.5-1 cm), preadults (1-2.5 cm), and adults (2.5-4 cm). The paddy cultivation system can affect the golden snail population. The purpose of this study was to determine the density, distribution and population structure of the golden snail (Pomacea canaliculata L.) with case studies in Cicalengka (conventional field) and Ciparay (organic field), District of Bandung, from October 2020-January 2021. This research used survey method with sampling technique in purposive sampling. At each location divided into 5 fields with sized 10x5 m which were divided into 7 quadrant plots. Sampling was carried out at the age of paddy crops 14,21,28, and 35 days after planting. The observerd parameters were density, distribution pattern using the Index of Morisita (Id) and population structure of P. canaliculata. The results showed that the density of P. canaliculata in organic field was higher than in conventional field. The average population structure of pre-adult golden snails in organic and conventional rice fields was significantly different at 14-35 days after planting (DAP) and adult golden snails at 14, 28, and 35 DAP. Distribution pattern of P. canaliculata in organic and conventional were grouped.